Treatment of Postinflammatory Hyperpigmentation Following Acne With Microneedling and Panax Ginseng–Derived Exosomes - Jovian Wan, MBChB; Soo-Bin Kim, PhD; Song Eun Yoon, MD; Hugues Cartier, MD; Sebastien Garson, MD; Kyu-Ho Yi, MD, PhD (Plastic and Reconstructive Surgery, Global Open, 2025)
Summary:. This case report evaluated the efficacy of microneedling therapy system (MTS) combined with topical exosome therapy for the treatment of postinflammatory hyperpigmentation (PIH) following acne. Two patients were included in the study: a 32-year-old woman with scattered PIH on her forehead, cheeks, nose, and perioral area, and a 37-year-old man with hyperpigmentation on both cheeks. Both patients underwent 3 sessions of MTS spaced 3 weeks apart, followed by the immediate application of a topical exosome (P198 RECORE SB PLUS, P198 ExoNature, Primoris International Co., Ltd., Seoul, Republic of Korea). PIH severity was assessed using the PIH severity scale, with baseline scores of grade 2 (mild) for both patients. One month after the final session, posttreatment scores improved to grade 1 (trace) for both patients, as evaluated by 2 dermatologists. Both patients demonstrated significant improvements in hyperpigmentation and overall skin tone. The female patient achieved a more even complexion with visible lightening in affected areas, whereas the male patient experienced a marked reduction in cheek pigmentation. Both patients expressed high satisfaction with the results, and no adverse effects were reported. These findings suggest that the combination of MTS and topical exosomes is a promising, safe approach for managing PIH, particularly in individuals with darker skin types prone to pigmentation disorders.